Identification of antiparasitic drug targets using a multi-omics workflow in the acanthocephalan model - Schmidt, Hanno; Mauer, Katharina; Glaser, Manuel; Dezfuli, Bahram Sayyaf; Hellmann, Sören Lukas; Silva Gomes, Ana Lúcia; Butter, Falk; Wade, Rebecca C.; Hankeln, Thomas; Herlyn, Holger (BMC genomics, 2022)
With the expansion of animal production, parasitic helminths are gaining increasing economic importance. However, application of several established deworming agents can harm treated hosts and environment due to their low specificity. Furthermore, the number of parasite strains showing resistance is growing, while hardly any new anthelminthics are being developed. Here, we present a bioinformatics workflow designed to reduce the time and cost in the development of new strategies against parasites. The workflow includes quantitative transcriptomics and proteomics, 3D structure modeling, binding site prediction, and virtual ligand screening. Its use is demonstrated for Acanthocephala (thorny-headed worms) which are an emerging pest in fish aquaculture. We included three acanthocephalans (Pomphorhynchus laevis, Neoechinorhynchus agilis, Neoechinorhynchus buttnerae) from four fish species (common barbel, European eel, thinlip mullet, tambaqui).
Gesehen am 10.01.2023